2016
DOI: 10.1097/ccm.0000000000001869
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Count Trends and Prevalence of Heparin-Induced Thrombocytopenia in a Cohort of Extracorporeal Membrane Oxygenator Patients

Abstract: Prevalence of heparin-induced thrombocytopenia and heparin-induced thrombocytopenia-related thrombosis among extracorporeal membrane oxygenator patients at our institution is relatively high. Using platelet count trends to guide decision to test for heparin-induced thrombocytopenia is not an optimal strategy in extracorporeal membrane oxygenator patients. Without a validated pretest probability clinical score, serosurveillance in a defined high-risk group of extracorporeal membrane oxygenator patients may be n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 30 publications
5
57
0
Order By: Relevance
“…The percentage of decreasing of the platelet count was mentioned in 7 papers [6-8, 16, 28, 29, 31]. Thrombocytopenia in V-A ECMO patients has been reported in 6 studies [8,24,25,31,36,40]. The I 2 test result showed high heterogeneity also in this sub-group analysis.…”
Section: • Thrombocytopeniamentioning
confidence: 73%
See 3 more Smart Citations
“…The percentage of decreasing of the platelet count was mentioned in 7 papers [6-8, 16, 28, 29, 31]. Thrombocytopenia in V-A ECMO patients has been reported in 6 studies [8,24,25,31,36,40]. The I 2 test result showed high heterogeneity also in this sub-group analysis.…”
Section: • Thrombocytopeniamentioning
confidence: 73%
“…There were 6.698 V-A ECMO patients, of whom 459 were post-cardiotomy. In 6 studies, authors did not report about the ECMO setting (post-cardiotomy, post-acute myocardial infarction, or other aetiologies) [8,16,25,26,28,39]. V-V ECMO was present in 477 patients.…”
Section: Study Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sokolovic et al reported that in a cohort of adult ECMO patients, eight of 96 patients were positive for HIT (positive SRA or H/PF4 ELISA with OD >1) and seven of those patients had documented thrombotic events (HITT) based on predefined criteria (HIT and HITT incidence in the study group of 8.3% and 7.3%, respectively). HIT‐positive patients were significantly younger and had a trend toward higher average HIT ELISA OD.…”
Section: Hit and Ecmomentioning
confidence: 99%